Implementation and Performance Analysis of 3-Phase Motor Rotation Left & Right - Deitje S. Pongoh; Arnold R. Rondonuwu; Leony A. Wenno; Refaldi Muaya; Alfian Aldo Pioh; Arther Rumbay; Jesica A.G Moningka; Christiano I.T Najoan; Gerald A. Kalalo (Interdisciplinary Journal of Advanced Research and Innovation, 2025)
This article will offer a fresh perspective on what it would be like to include a 3-phase motor that spins left and right into a device and how to assess the performance that would arise from doing so. We will discuss a few items: 1) What is a left- and right-rotating 3-phase motor? 2) How can a tool or system incorporate left and right-rotating 3-phase motors? 3) What happens when left and right-rotating 3-phase motors are used? 4) Performance analysis and the things to consider if we use a three-phase motor with left and right rotation. This journal will be expanded to make it more understandable and beneficial to all readers. It is based on several current studies and discoveries.